Therapeutic Exercise: Foundations and Techniques - Kisner, Carolyn and Colby, Lynn Allen (Princeton, N.J. Recording for the Blind & Dyslexic, 2009)
Offers guidelines for managing musculoskeletal conditions. This work also provides principles of therapeutic exercise and manual therapy. It describes pathologic conditions and surgical procedures commonly encountered by therapists in the clinical setting.
Includes Colored Illustrations and Index.
Keywords: Exercise therapy -- Handbooks, manuals, etc